2011
DOI: 10.1124/dmd.110.037853
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib and Sunitinib, Two Anticancer Drugs, Inhibit CYP3A4-Mediated and Activate CY3A5-Mediated Midazolam 1′-Hydroxylation

Abstract: ABSTRACT:Sorafenib and sunitinib are novel small-molecule molecularly targeted anticancer drugs that inhibit multiple tyrosine kinases. These medicines have shown survival benefits in advanced renal cell carcinomas as well as in advanced hepatocellular carcinomas and gastrointestinal stromal tumors, respectively. The effects of sorafenib and sunitinib on midazolam 1-hydroxylation catalyzed by human CYP3A4 or CYP3A5 were investigated. Sorafenib and sunitinib inhibited metabolic reactions catalyzed by recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…Sorafenib and sunitinib have also been reported to activate the formation of 19-hydroxymidazolam (Sugiyama et al, 2011;Kenny et al, 2012), but this was not observed in our incubations. The heteroactivation mechanism for these kinase inhibitors has been reported to be substratedependent, as it has been observed with midazolam but not with the other CYP3A marker substrates nifedipine and testosterone (Li et al, 2007;Dong et al, 2011;Kenny et al, 2012).…”
Section: Variablecontrasting
confidence: 51%
See 1 more Smart Citation
“…Sorafenib and sunitinib have also been reported to activate the formation of 19-hydroxymidazolam (Sugiyama et al, 2011;Kenny et al, 2012), but this was not observed in our incubations. The heteroactivation mechanism for these kinase inhibitors has been reported to be substratedependent, as it has been observed with midazolam but not with the other CYP3A marker substrates nifedipine and testosterone (Li et al, 2007;Dong et al, 2011;Kenny et al, 2012).…”
Section: Variablecontrasting
confidence: 51%
“…The heteroactivation mechanism for these kinase inhibitors has been reported to be substratedependent, as it has been observed with midazolam but not with the other CYP3A marker substrates nifedipine and testosterone (Li et al, 2007;Dong et al, 2011;Kenny et al, 2012). It is not clear whether the activation by erlotinib and gefitinib occurs via CYP3A4 or CYP3A5, but for sorafenib and sunitinib it is reported to occur via CYP3A5 (Sugiyama et al, 2011). In the present study, we did not differentiate between CYP3A4 and CYP3A5, but the lack of stimulation of midazolam 19-hydroxylation by sorafenib and sunitinib suggests that CYP3A4 activity was more prominent than that of CYP3A5 in the HLM batch used.…”
Section: Variablementioning
confidence: 91%
“…The latter strongly inhibited CYP3A4 while also being metabolized by it. However, there are few reports about the inhibition of specific P450 isoenzymes by antitumor agents, eg, by thiotepa [42,43] , tamoxifen [44,45] and the less well-known sorafenib [46] . Our results showed that cytochrome P450 CYP3A4 did not metabolize C-1311 in cells, confirming our hypothesis that overexpression of this enzyme might modulate the cellular response of CHO cells following C-1311 treatment, even though CYP3A4 does not participate in metabolic transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotropic positive cooperativity may also explain the interaction of thalidomide with midazolam in human CYP3A5 in which thalidomide increased midazolam 1Ј-hydroxylation and total midazolam oxidation (Okada et al, 2009). Midazolam 1Ј-hydroxylation was shown to be activated by sorafenib and sunitinib in CYP3A5 (Sugiyama et al, 2011) and ticagrelor in HLM (Zhou et al, 2011).…”
Section: Effect Of Efavirenz On the Midazolam 1ј-hydroxylation By Hlmmentioning
confidence: 99%